Loss of ctnnd2b affects neuronal differentiation and behavior in zebrafish - Vaz, Raquel; Edwards, Steven; Dueñas-Rey, Alfredo; Hofmeister, Wolfgang; Lindstrand, Anna (Frontiers in Neuroscience, 2023)
Delta catenin (CTNND2) is an adhesive junction associated protein belonging to the family of p120 catenins. The human gene is located on the short arm of chromosome 5, the region deleted in Cri-du-chat syndrome (OMIM #123450). Heterozygous loss of CTNND2 has been linked to a wide spectrum of neurodevelopmental disorders such as autism, schizophrenia, and intellectual disability. Here we studied how heterozygous loss of ctnnd2b affects zebrafish embryonic development, and larvae and adult behavior. First, we observed a disorganization of neuronal subtypes in the developing forebrain, namely the presence of ectopic isl1-expressing cells and a local reduction of GABA-positive neurons in the optic recess region. Next, using time-lapse analysis, we found that the disorganized distribution of is1l-expressing forebrain neurons resulted from an increased specification of Isl1:GFP neurons. Finally, we studied the swimming patterns of both larval and adult heterozygous zebrafish and observed an increased activity compared to wildtype animals. Overall, this data suggests a role for ctnnd2b in the differentiation cascade of neuronal subtypes in specific regions of the vertebrate brain, with repercussions in the animal’s behavior.